Empirical network contagion for U.S. financial institutions - Fernando Duarte; Collin Jones (Federal Reserve Bank of New York, 2017)
We construct an empirical measure of expected network spillovers that arise through default cascades for the U.S. financial system for the period 2002-16. Compared to existing studies, we include a much larger cross section of U.S. financial firms that comprises all bank holding companies, all broker-dealers, and all insurance companies, and consider their entire empirical balance sheet exposures instead of relying on simulations or on exposures arising just through one specific market (like the fed funds market) or one specific financial instrument (like credit default swaps). We find negligible expected spillovers from 2002 to 2007 and from 2013 to 2016. However, between 2008 and 2012, we find that default spillovers can amplify expected losses by up to 25 percent, a significantly higher estimate than previously found in the literature.
Keywords: D85; G21; 330; systemic risk; contagion; financial network